Potential of a bacterial consortium to degrade azo dye Disperse Red 1 in a pilot scale anaerobic-aerobic reactor - Franciscon, Elisangela; Mendonca, Danilo; Seber, Samile; Morales, Daniel Alexandre; Zocolo, Guilherme Juliao [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP]; Grossman, Matthew James; Durrant, Lucia Regina; Freeman, Harold S.; Umbuzeiro, Gisela Aragao (Elsevier B.V., 2015)
The textile industry is the largest consumer of azo dyes and activated sludge treatment systems typically used to remove them are frequently inefficient, resulting in significant quantities of these compounds adsorbed in the sludge or released into water bodies. The aim of this study was to evaluate the biodegradation of the commercial azo dye Disperse Red 1 in a pilot scale anaerobic-aerobic reactor inoculated by a microbial consortium selected for its capacity to degrade azo dyes. Dye decolorization (80%) occurred in 60 h in the anaerobic reactor and 92% COD (chemical oxygen demand) was removed as measured in the treated effluent. LC-ESI-MS/MS of the treated effluent showed the formation of a reduced azo bond and azo bond cleavage and subsequent degradation products. Aromatic amines produced by the cleavage of the azo bond were not detected. Toxicity tests performed with Daphnia similis and Hydra attenuate in the treated effluent showed that the toxicity was reduced significantly. Mutagenicity, evaluated using the Salmonella/microsome Ames test, found the untreated dye medium was only mutagenic toward Salmonella strain YG1041. However after treatment, only marginal mutagenicity was observed. These results indicate the bacterial consortium was effective in biodegrading Disperse Red 1 and also reducing the toxicity and mutagenicity and may represent a promising application for dyes biodegradation. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Disperse Red 1; Bioreactor; Biodegradation; Microbial consortium; Metabolites; Toxicity